A review on mechanization of traditional dairy products - Talwar, Gopika; Brar, Sandeeppal Kaur (Indian Journal of Dairy Science, 2017)
India is the largest milk producing nation in the world. Milk is perishable in nature, thus it cannot be stored for a very long period. In order to preserve it, more than half of milk produced in India is converted into a variety of traditional value added milk products which played a significant role in the Indian economy. Traditional milk products have a distinct advantage of being value added products, mass appeal, give high profit margins and have high export potential. Indian traditional dairy products are largely classified into 5 broad categories i.e. Heat desiccated products, acid coagulated, cultured or fermented, fat rich and milk based deserts . Increasing demand for these products in India as well as global market present a great opportunity for the organized dairies in the country to modernize and scale-up the production. There has been significant development and mechanization in dairy sector in past few years. It has transformed various processes for dairy products from traditional energy and labour intensive processes to mechanized processes where human interference is minimized. In this article various researches and adoptions done for mechanization of various dairy processes is reviewed. This will help in knowing products where mechanization has taken place and will help researchers to target where mechanization is further required and also help entrepreneurs to upgrade themselves from traditional system to available mechanized system.